Contextualizing Probability Tasks: The Case of Egyptian School Curriculum - Elbehary, Samah Gamal Ahmed (International Journal on Emerging Mathematics Education, 2023)
This paper clarifies contexts of probability in Egyptian primary and lower-secondary school textbooks and how the students prioritize them. Through a preliminary general inductive analysis, it was apparent that the Egyptian curriculum emphasized the conventional activities that require calculations and are suitable to employ theoretical probability. On the other hand, students highlighted the environmental circumstances, such as predicting the weather, to be the most practical context for the probability. Accordingly, refinement of the curriculum is needed to be consistent with students’ viewpoints.